Influence of drought and heat stresses in fodder legumes productivity and nutritive value - Nour Ressaissi; Maria Teresa Sanchez-Ballesta; Mounawer Badri (Journal of Oasis Agriculture and Sustainable Development, 2023)
Plants are often subjected to several environmental constraints in the field, often simultaneously, which significantly affect their productivity. Among these constraints, water deficit and heat stress are the main constraints limiting plant yield in the arid regions of the Mediterranean basin. Both of these abiotic factors are exacerbated by climate change. Fodder legumes provide a rich resource of plant nutrition to human diets, and are vital for food security and sustainable cropping. Numerous biochemical, molecular, and physiological responses are evoked by drought and heat stresses, influencing the fodder crop yield and nutritional value. When plants are water stressed, they are unable to maintain good growth and produce high yields. Drought also reduces the protein content of the plants, which can lead to a decrease in forage quality. Heat can negatively affect the productivity of forage legumes. High temperatures can cause heat stress which can lead to decreased photosynthesis and reduced productivity. In addition, high temperatures can result in decreased forage quality and increased nutrient losses. Exposure to combined water stress and heat can reduce the protein, fiber and mineral content of forage legumes and can also reduce their digestibility. This review summarizes the current status of the effects of drought and heat stresses on forage crops productivity and fodder quality.